'Because Christian was mean and killed innocent people!': Swedish primary school students' causal reasoning about the origins of the nation. Issue 5 (3rd September 2017) - Samuelsson, Johan; Wendell, Joakim
ABSTRACT: The topic of this article is how Swedish primary school students aged 12–13 use causal reasoning when they explain a historical event that is usually considered the 'origin of the nation'. The study is based on student texts about the rise to power of Gustav Vasa, who is traditionally portrayed as the 'founding father' of Sweden. The analysis of the students' causal reasoning takes into account how many, and what kinds of, causal factors the students use. The main finding of the study is that one category of students give causal explanations that adhere very close to the traditional image of the event, with Vasa as an important and heroic agent pitted against an antagonist, king Kristian II. Another category of students instead give generic explanations with very little historical context. Of these, the former category shows greater causal complexity than the latter. In both categories, there are instances of students failing to causally connect agents to the event, suggesting that teaching practices may need to address this issue.